Relabelling behaviour. The effects of psycho‐education on the perceived severity and causes of challenging behaviour in people with profound intellectual and multiple disabilities. Issue 12 (18th May 2016) - Poppes, P.; van der Putten, A.; Post, W.; Frans, N.; ten Brug, A.; van Es, A.; Vlaskamp, C.
Abstract: Background: Prevalence rates of challenging behaviour are high in children and adults with profound intellectual and multiple disabilities (PIMD). Moreover, many of these behaviours are observed daily. Direct support staff report that most challenging behaviour identified has little impact on the person with PIMD and attribute challenging behaviour in children and adults with PIMD mainly to a biomedical model. The purpose of this study was to evaluate whether an intervention (psycho‐education) had any effect on direct support staff's assessment of challenging behaviour in terms of its severity and their biomedical causal explanations (attributions) for this behaviour. Method: A stepped wedge study design was used to evaluate the effects of a psycho‐education intervention on the perceived severity and the attributions offered for challenging behaviour of people with PIMD by 198 direct support staff. We used questionnaires assessing the perceived severity of challenging behaviour and staff views of its causes. Data on the dependent variables were collected at four 1‐month intervals. Results: The intervention was found to have an effect on the perceived severity of challenging behaviour identified in people with PIMD in the sense that staff generally scored challenging behaviour as more severe in its consequences after the intervention. However, this effect was very small. No significant effects were found in terms of reduction in the biomedical scale scores. Conclusion: No evidence for the effectiveness of a psycho‐educational approach on the assessment of challenging behaviour in terms of severity and the biomedical attributions for behaviour was found. More research is required to explore further the effects of more elaborate training using methods to enable direct support staff to reflect on the behaviour of people with PIMD and on their own behaviour.